Numerical study of interactive ingress of calcium leaching, chloride transport and multi-ions coupling in concrete. (March 2023) - Liu, Qing-feng; Shen, Xiao-han; Šavija, Branko; Meng, Zhaozheng; Tsang, Daniel C.W.; Sepasgozar, Samad; Schlangen, Erik
Abstract: In circumstances with wastewater and seawater, the behavior of multi-ions including calcium, chloride and others in concrete attracts attention. The present study investigated the multiple mechanisms that could happen under the special field situation above, including calcium leaching, chloride transport and multi-ion coupling. To realize the interactive ingress of multi ions, the simulation method for the processing of the individual mechanisms and the mutual influences is adopted. The distributions of the diversified ions are analyzed with the influence of the interfacial transition zone. The time-spatial distribution of porosity and its evolution mechanisms are investigated by considering the interaction with calcium ions in both pore solution and solid phase. The results indicate that calcium leaching would dominantly speed up chloride transport due to the coarsened pore structure, while the multi ions electrochemical coupling effect would facilitate calcium leaching in the early stage but subtly delay calcium leaching in the later stage.